Pendekatan Kolaboratif dalam Menangani Konflik Spasial Kawasan Pesisir di Pantai Selatan Yogyakarta - Iwan Darmawan; Ikaputra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2021)
Title: A Collaborative Approach to Handling Coastal Spatial Conflicts in Yogyakarta Southern Coast Yogyakarta's southern coastal ecosystem is facing increasing impacts from fisheries, aquaculture, tourism, energy production, shipping, pollution, climate change and other stressors. This paper discusses the importance of collaborative planning, more than community-based in coastal tourism areas as well as mangrove forest conservation areas, as well as environmental stressors in the form of shrimp ponds. The purpose of this paper is to analyze the understanding of the type of planning approach that is most appropriate, namely collaborative in areas that have spatial conflicts. The method used in this paper is a literature study which describes the theory, findings, and other research materials obtained from reference material to be used as a research basis by compiling a clear framework from the formulation of the problem to be studied. coupled with field observations. The author then provides a review, summary, and dialogue about the theory which is then used to build a relevant theoretical framework. Literature references used are related to collaborative planning and coastal tourism. Based on the discussion that has been done, it can be concluded that to overcome spatial conflicts in the southern coastal tourism area of ??Yogyakarta, this type of planning with a collaborative approach is the most appropriate to be applied wherein the process involves stakeholders with the ultimate goal of a collective agreement for all parties and with a sustainable perspective.